Laporan keuangan organisasi nonlaba: studi kasus pusat rehabilitasi YAKKUM tahun 2019 - Dwi Urip Wardoyo; Ismi Raihan Nadhira; Mutia Afiqah; Ninit Megalia Pransisca; Syifa Khoerunnisa (Jurnal Riset Pendidikan Ekonomi, 2023)
Contributions made by non-profit organizations in carrying out social change need to be given special attention. With the role of non-profit organizations in supporting inclusive community programs, the parties involved such as organizational members and fund developers need to unite activities, especially in terms of distributing funds. This study aims to observe the financial statements of the non-profit organization YAKKUM in managing programs for people with disabilities in 2019. The standard used in this study is a financial report based on ISAK 35. The results of this study are that the non-profit organization YAKKUM still has deficiencies in their reports when viewed based on implementing ISAK 35, so there is needed to increase quality and consistency in presenting financial reports.